Why women with advanced carcinoma cervix do not seek medical help early: a tertiary hospital based Indian study - Raheja, Aastha; Agarwal, Krishna; Ravi, Anoosha K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Cervical cancer is a disease which claims maximum number of deaths in developing countries. Objective of this study was to understand the reason for delayed approach to medical help in women with advanced carcinoma cervix. Methods: It was a cross-sectional study. Information obtained from women with carcinoma cervix clinical stage IIb and above with proven histopathological diagnosis was recorded in the predetermined format. Results: Almost all the subjects were illiterate and were from lower socioeconomic strata and rural areas. None of them knew about the disease and its symptomatology. About 82% of the patients were symptomatic since 5-10 years however took no medical care during the period and 2/3rd of them even did not reveal their problem to any of the family members. About 79% of the subjects had never used any contraception and none had knowledge about its role in preventing infection. Majority of them (98%) had no idea about the role of PAP smear in screening carcinoma cervix. All of them said if they had knowledge about the disease, they would have sought medical help much earlier. Conclusions: The most important reason for delayed approach in our study was found to be lack of knowledge about the disease. Therefore, till such time that we have national screening program in place, these women who are at high risk of developing carcinoma of cervix should be targeted and educated through mass media so that these women could seek medical help in early stages.